Bipolar affective disorder with obsessive-compulsive symptoms: case report and nursing care plan - Olczak, Katarzyna; Maliszewska, Weronika (Nursing Problems / Problemy Pielęgniarstwa, 2026)
Bipolar affective disorder (BD) is a chronic psychiatric condition characterized by recurrent episodes of depression, mania, or hypomania. Its course significantly reduces quality of life and increases suicide risk. The coexistence of obsessive-compulsive disorder exacerbates anxiety symptoms and complicates both diagnosis and treatment. The aim of this study was to present a case of a female patient hospitalized due to BD with comorbid obsessive-compulsive disorder (OCD) and to develop a nursing care plan based on the International Classification for Nursing Practice (ICNP). The research material included medical records and nursing observations. The 48-year-old patient demonstrated severe depressive and compulsive symptoms, including avoidance of meals and compulsive handwashing, which resulted in self-care deficits and weight loss. The individualized care plan focused on safety monitoring, emotional support, psychoeducation, sleep hygiene, and activation. Hospitalization led to mood improvement, anxiety reduction, and greater patient engagement in therapy. This case highlights the crucial role of psychiatric nurses in interdisciplinary care.